Les lendemains de l'arrêt Kravitz : la responsabilité du fabricant dans une perspective de réforme - Rousseau-Houle, Thérèse (Les Cahiers de droit, 1980)
In the milestone case of Kravitz v. General Motors, the Supreme Court of Canada has recently confirmed that a contract of sale confers on the buyer a right of action against the manufacturer, as distinct from the seller, under the legal warranty against latent defects. The obligation to answer for latent defects is inherent in the sale, and the action to enforce that obligation becomes available, as a incidental right, to subsequent owners of the thing sold, who may proceed directly against the manufacturer. This important case reinforces the prevalent tendency in Quebec case-law and legal writing towards better safeguards for the consumer. Interesting vistas are opened in this paper by comparing the principles underlying the Supreme Court's decision in Kravitz with French and American rules on manufacturer's liability. This exercise further highlights the significance of Kravitz in regard of the present state of the law and of legislative reforms currently under consideration.